From SARS to COVID-19: What lessons have we learned?. Issue 11 (November 2020) - Liu, Qin; Xu, Kaiyuan; Wang, Xiang; Wang, Wenmei
Abstract: After the outbreak of severe acute respiratory syndrome (SARS) in November 2002, coronaviruses (CoVs) received worldwide attention. On December 1, 2019, the first case of coronavirus disease 2019 (COVID-19), caused by a novel coronavirus (SARS-CoV-2), was reported in Wuhan, China, and CoVs returned to public view. On January 30, 2020, the World Health Organization (WHO) declared that the COVID-19 epidemic is a public health emergency of international concern (PHEIC), and on March 11, 2020, the WHO classified COVID-19 as a pandemic disease. As of July 31, 2020, COVID-19 has affected 216 countries and regions, with 17, 064, 064 confirmed cases and 668, 073 deaths, and the number of new cases has been increasing daily. Additionally, on March 19, 2020, there were no new confirmed cases in China, providing hope and valuable experience for the international community. In this review, we systematically compare COVID-19 and SARS in terms of epidemiology, pathogenesis and clinical characteristics and discuss the current treatment approaches, scientific advancements and Chinese experience in fighting the epidemic to combat the novel coronavirus pandemic. We also discuss the lessons that we have learned from COVID-19 and SARS.